2019
DOI: 10.2147/opth.s191887
|View full text |Cite
|
Sign up to set email alerts
|

<p>Retrospective analysis of an intraoperative aberrometry database: a study investigating absolute prediction in eyes implanted with low cylinder power toric intraocular lenses</p>

Abstract: Purpose To evaluate the spherical equivalent outcomes of intraoperative aberrometry (IA) power calculations compared with the surgeons’ preoperative power calculations in eyes implanted with AcrySof ® IQ T3 intraocular lenses (IOLs). Patients and methods We assessed data collected by an IA system from multiple centers in the United States. Data was from patients who had undergone cataract extraction by phacoemulsification with the use of the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…The percentage of eyes with a mean absolute prediction error of 0.5 D or less was higher with IA (89.4%) compared to preoperative calculations (85.4%), a significant difference of 4%. This difference is similar to the differences reported by Cionni et al, 5 Cionni et al, 6 and Woodcock et al 9 of 6%, 6.9%, and 1.8%, respectively. These three studies used multiple surgeons, differing preoperative formulas, and larger datasets, which could explain the differences observed in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The percentage of eyes with a mean absolute prediction error of 0.5 D or less was higher with IA (89.4%) compared to preoperative calculations (85.4%), a significant difference of 4%. This difference is similar to the differences reported by Cionni et al, 5 Cionni et al, 6 and Woodcock et al 9 of 6%, 6.9%, and 1.8%, respectively. These three studies used multiple surgeons, differing preoperative formulas, and larger datasets, which could explain the differences observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“… 5 A separate study using low-power toric IOLs also reported that IA resulted in a lower prediction error (SE) than preoperative planning. 6 However, other studies have reported no significant differences in prediction error (SE) between IA and preoperative planning. 7–9 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A couple studies of large datasets reported that IA resulted in a higher percentage of patients with absolute prediction error 0.5 D or less compared to preoperative planning. 13 , 14 However, there are also reports of minimal difference in absolute prediction error between preoperative planning and IA. 15–18 In addition, the percentages of eyes with absolute prediction error of 0.5 D or less was greater in this study for both IA and preoperative planning compared to other studies of post-LVC eyes with non-trifocal 6 , 19 and trifocal 7 , 8 IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…As more modern IOL formulas improve, many of the pre-existing IA studies are becoming less informative. While IA has been shown to improve refractive accuracy for many patients, 4 , 15 , 16 most comparisons that achieved statistical significance are comparisons with non-standardized aggregates of formulas or specifically comparing to “older” formulas such as Holladay 1, Holladay 2, and SRK/T. Comparison with newer formulas has shown that IA is equal or worse than the Barrett Universal II or Hill-RBF.…”
Section: Discussionmentioning
confidence: 99%